2020
DOI: 10.1029/2019ja027678
|View full text |Cite
|
Sign up to set email alerts
|

On Energetic Electron Dynamics During Geomagnetic Quiet Times in Earth's Inner Radiation Belt due to Atmospheric Collisional Loss and CRAND as a Source

Abstract: To investigate the role of atmospheric collisions and cosmic ray albedo neutron decay (CRAND) in the dynamics of energetic electrons in the Earth's inner radiation belt during geomagnetic quiet times, a drift‐collision‐source model that includes azimuthal drift, pitch angle diffusion from elastic collision, energy loss from inelastic collision, and a CRAND source is developed. In the model, the bounce‐averaged pitch angle diffusion coefficients and energy loss rates are calculated based on scattering of electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…It is clearly shown that the combined scattering due to VLF transmitter waves, lightning-generated whistlers, plasmaspheric hiss, and magnetosonic waves can systematically reproduce the key features of the formation and evolution of the bifurcated electron belt. However, the energetic electron flux decay at L <~1.8 is not well captured by the simulation, which is likely attributed to loss by atmospheric collision 17,41 . Pitch angle scattering by VLF transmitter waves dominates the decay of tens of keV electrons at L~1.8-2.4 during the 14-day period.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…It is clearly shown that the combined scattering due to VLF transmitter waves, lightning-generated whistlers, plasmaspheric hiss, and magnetosonic waves can systematically reproduce the key features of the formation and evolution of the bifurcated electron belt. However, the energetic electron flux decay at L <~1.8 is not well captured by the simulation, which is likely attributed to loss by atmospheric collision 17,41 . Pitch angle scattering by VLF transmitter waves dominates the decay of tens of keV electrons at L~1.8-2.4 during the 14-day period.…”
Section: Methodsmentioning
confidence: 86%
“…It is noteworthy that the energetic electron flux decay at L-shell of 1.5-1.7 is not well captured by the simulations. At these low L-shells, the typical cyclotron resonant electron energies due to VLF transmitter waves are above 100 keV, and losses by an atmospheric collision can potentially play an important role in modulating the electron dynamics 17,41 . Moreover, we performed simulations by using the statistical wave amplitude profile of VLF transmitter waves during the northern hemisphere winter, the results of which are presented in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the conclusion in Albert et al (2020) that energy diffusion is a significant source of energetic electrons in the slot region may not be applicable during extended quiet times. Different from the source due to energy diffusion, which is strongly dependent on the boundary condition and the energy spectrum, the CRAND source is relatively constant and can be quantitatively determined by the flux level of quasi‐trapped electrons (Xiang et al, 2019, 2020; Zhang, Li, et al, 2019). Based on the drift‐diffusion‐source model, we demonstrated that CRAND is an important source of relativistic electrons in the slot region during extended quiet times.…”
Section: Discussionmentioning
confidence: 99%
“…The wave information used to calculate <D αα > is summarized in Table 1. Collisions between electrons and atmospheric species can also induce PA diffusion. Generally, atmospheric scattering dominates the loss of relativistic electrons at L < 1.3 (e.g., Walt, 1964), while wave-particle interactions become more important at higher L. In this study, we have calculated the bounce-averaged PA diffusion coefficients from atmospheric scattering following formulas in previous studies (Cunningham et al, 2018;Selesnick, 2012;Xiang et al, 2020) with inputs from the NRLMSISE-00 model (Picone et al, 2002) and the International Reference Ionosphere (IRI) 2012 (Bilitza et al, 2014).…”
Section: Calculation Of Pa Diffusion Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation